BAHTSUL MASAIL SEBAGAI PEMBELAJARAN KONTEKSTUAL SANTRI DI PON-PES DARUSSALAM SUMBERSARI KEDIRI - Ida Ansori (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2023)
This study aims to explore Bahtsul Masail as a contextual learning method at the Darussalam Islamic Boarding School in Sumbersari, Kediri. Bahtsul Masail is a scholarly discussion forum that addresses religious issues based on the study of classical Islamic texts (kitab kuning). This research employs a qualitative approach to understand how Bahtsul Masail is applied as part of the learning system in the pesantren. Data were collected through in-depth interviews, participatory observations, and documentation. The findings indicate that Bahtsul Masail not only plays a role in deepening students' religious knowledge but also equips them with critical thinking, argumentation skills, and the ability to solve problems contextually. This learning method is relevant to the socio-religious challenges faced by students in their daily lives, creating an adaptive and applicable learning model in the pesantren environment